Bukti Kebijakan Dividen: CR, DER, ROE, dan TATO Perusahaan LQ-45 yang Terdaftar di JII - Hadi, Hadi Isman; Guntur, Guntur Kusuma Wardana; Barlian, Noer Aisyah Barlian; Riza, Muhammad Riza Hafizi (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2025)
In the current era of world development, there are also many things that have undergone development, in addition to the technology sector, the economic sector has also experienced quite rapid development. One of the institutions that plays an important role in economic development is the capital market institution which is an intermediary for companies that need additional capital to meet with investors who have more money and want to invest their money in certain companies. In addition, every country in the world will do efficiency or eliminate high-cost economics, in order to be able to compete in price. One way to reduce high costs is to lead private companies into the capital market so that the company's capital structure becomes better, more efficient, and more controlled by the community. The purpose of this study is to determine the influence of the variables current ratio (CR), dept to equity ratio (DER), return on equity (ROE) and total assets turnover (TATO) partially and simultaneously on the dividend policy in LQ45 companies listed on JII. The method used is a descriptive quantitative approach. The object of the study is companies listed in the LQ-45 index which is also listed in the Jakarta Islamic Index (JII). The results of the study show that partially each of the CR, DER and TATO variables has a significant influence on the House of Representatives on LQ-45 companies listed in the Jakarta Islamic Index (JII). Meanwhile, the ROE variable has no effect on the House of Representatives for LQ-45 companies listed in the Jakarta Islamic Index (JII). The variables Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE) and Total Assets Turnover (TATO) have a significant influence on the Dividend Payout Ratio (DPR) in LQ-45 companies listed in the Jakarta Islamic Index (JII).